Enhancing Classroom Engagement and Academic Achievement through the Implementation of Cooperative Learning Strategies: A Comparative Study in Secondary Education - Mustakim, Mustakim; Salija, Kisman; Basri, Muhammad (Sublim: Jurnal Pendidikan, 2023)
This comparative study explores the impact of cooperative learning strategies on classroom engagement and academic achievement in secondary education. Employing a quasi-experimental research design, the research involves a diverse group of secondary school students and teachers. The experimental group experiences cooperative learning strategies, while the control group follows traditional teacher-centered methods. Findings reveal a significant increase in classroom engagement within the experimental group, marked by enhanced student participation and a positive learning atmosphere. Academic achievement shows notable improvements, emphasizing the efficacy of cooperative learning in fostering deeper understanding and critical thinking skills. Teacher perspectives undergo positive shifts, reflecting increased job satisfaction, while students express a preference for the collaborative nature of cooperative learning. Positive changes in group dynamics, contextual considerations such as class size, and the crucial role of teacher commitment emerge as significant factors. The study underscores the transformative potential of cooperative learning in secondary education and advocates for its integration into educational policies and ongoing professional development initiatives.